1982
DOI: 10.1128/iai.35.2.605-611.1982
|View full text |Cite
|
Sign up to set email alerts
|

Serum resistance associated with virulence in Yersinia enterocolitica

Abstract: Yersinia enterocolitica strains that exhibited a calcium requirement for growth and autoagglutination at 37°C were invariably virulent in rabbits, causing diarrhea and a high degree of lethality, and were capable of colonizing the intestinal lumen and establishing foci of infection on the Peyer's patches of mice. Strains that had lost the properties of calcium dependency and autoagglutinability were totally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 23 publications
3
85
0
Order By: Relevance
“…Previous reports have shown that Y. enterocolitica serotype 08 with the virulence plasmid has the ability to cause intestinal infection with persistent presence of viable yersiniae in the ileal contents, ileal tissue, and Peyer's patches [5,20]. We compared the virulent strain IP383 of serotype 09 and its plasmid-less derivative IP383p-for their abilities to survive in the Peyer's patches after oral challenge (Table 1).…”
Section: Survival Of Bacteria In the Peyer's Patchesmentioning
confidence: 99%
“…Previous reports have shown that Y. enterocolitica serotype 08 with the virulence plasmid has the ability to cause intestinal infection with persistent presence of viable yersiniae in the ileal contents, ileal tissue, and Peyer's patches [5,20]. We compared the virulent strain IP383 of serotype 09 and its plasmid-less derivative IP383p-for their abilities to survive in the Peyer's patches after oral challenge (Table 1).…”
Section: Survival Of Bacteria In the Peyer's Patchesmentioning
confidence: 99%
“…In a previously published communication on Y. enterocolitica ( 13), we reported the existence of a distinct MRHA, which was strictly correlated with ing (40-45 Mdal) derivative (P+), and its isogenic plasmid-cured mutant (P-), cultivated at 22 and 37 "C. All four strains show plasmid-associated OMPs expressed phenotypically only at 37 "C. Arrows indicate two prominent plasmid-associated OMPs, common to all strains and serogroups tested. Strains NY81-71 (03) and 3315 (0:9), unlike the 0:3 strains, show plasmid-independent OMPs (PIOMPs) which are expressed mainly at 22 "C. The abscissa indicates molecular weights in kilodaltons.…”
Section: Discussionmentioning
confidence: 80%
“…It was tested according to the method of Pai and DeStephano (1982). Bacterial cultures were washed twice in PBS and suspended to 5.0 · 10 3 CFU/ml in PBS.…”
Section: Serum Bactericidal Activitymentioning
confidence: 99%